How people bereaved by suicide perceive newspaper reporting: qualitative study. - Chapple, A; Ziebland, S; Simkin, S; Hawton, K (2013)
BACKGROUND: People bereaved by suicide are often reported to be distressed by media reporting. Current media guidelines for reporting suicide focus especially on prevention of copycat behaviour. AIMS: To explore bereaved individuals' experiences of media reporting after suicide and to examine their priorities in relation to media guidelines. METHOD: In-depth interviews with 40 people bereaved by suicide, with qualitative analysis. Review of four guidelines. RESULTS: There is a difference of emphasis between guidance for the press that aims to prevent copycat suicides (especially avoidance of details such as method used) and the perspectives of bereaved people (who prioritise sympathetic and accurate reporting, sometimes including details of the death and images of the person who died). We found that bereaved relatives were sometimes keen to talk to the press. Those who were upset by the press focused on careless reporting, misquoting and speculation that gave an inaccurate impression of the death. CONCLUSIONS: The Leveson Inquiry has drawn attention to the damage that can be caused by irresponsible journalism. Guidelines written to prevent 'copycat' suicides are important, but so are the needs of bereaved relatives. Because accuracy matters greatly to the bereaved, families should be able to work with an intermediary such as a police press officer to prepare a statement for the press to minimise the risk of misrepresentation.